Highlighting the leading companies of the world economy - O. V. Mikhailov (Вестник университета, 2019)
Objective and methodical identification of the best companies in the world economy and systematization of their competitive advantages allows to strengthen and improve their own competitiveness in order to outpace the leading competitors. The methods and criteria for the selection of hidden champions of the world market have been refined in the article, some of their important characteristics have been summarized. On the basis of the world theoretical and economic experience of international business leaders, some recommendations on the specifics and directions of analysis and study of their achievements have been given.